Visoko obrazovanje u doba pandemije: Stavovi studenata internacionalnog univerziteta u Sarajevu o online nastavi i povratku na nastavu u učionici / Higher Education in the Period of the Pandemic: International University of Sarajevo Students' Attitudes Towards Online Education and Returning to Face-To-Face Education - Jelešković, Emina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
In 2021 fall semester, students and professors of International University of Sarajevo resumed face-to-face education after the period of online classes during the COVID-19 pandemic. The aim of the paper is to determine attitudes of students towards online education and return to face-to-face education and their recommendations on how to improve higher education during the pandemic. The instrument used to collect data was a survey questionnaire that was filled-in online. The total number of 103 students filled-in the questionnaire (n=103). Quantitative and qualitative methodology were applied. Descriptive statistics was conducted with SPSS software. The qualitative method of content analysis was applied to answers to open-ended questions. The results show a polarization of students into those who prefer online education and those who prefer face-to-face education. For the students, the main advantages of returning to face-to-face classes are: more efficient learning, socializing with their peers, higher quality of classes, better communication and true university experience. The disadvantages are: the risk of COVID-19 infection, difficult time management, issues related to mental health and lectures. For students, online education meant more time, advantages of online lectures, higher security during the pandemic, less stress and lower costs, but also issues with computers and internet, lectures, exams, a lack of contact with their peers and more stress. In order to improve higher education, the students highlight the importance of adjusting it to the circumstances of the pandemic, improving the teaching process and the relations between professors and students, and keeping the focus on students' needs.